USING INTERNET RESOURCES IN MEDICAL EDUCATION TO TEACH THE SUBJECT OF ANATOMY (World Bulletin of Public Health, 2022)
Our society is undergoing, and probably will continue to undergo, changes in all aspects of life in the state, both political and socio-economic. All these progressive changes have affected the natural process of vocational education, which should be adjusted to the needs of society for highly qualified personnel with solid and profound knowledge capable of selfdevelopment and self-actualization. The education act states that the student has the right to receive the whole body of educational knowledge. The teacher of hei should form a highly qualified specialist - a citizen of the republic of uzbekistan, capable of an active life position, correctly oriented in the modern system of values of our society. The course work presents types and advantages of modern pedagogical technologies as one of the forms of innovative interactive learning for medical students studying the subject "human anatomy"
Keywords: Human Anatomy; Medical Students; Internet Resources